Clinical and developmental characteristics of sex offenders in Malaysian prisons - Aili, H.H.; KS, M.; Pillai, S.K.; Muhsin, M.; Salwina, W. (2012)
The population of incarcerated sex offenders in Malaysia is steadily growing. Objective: This is a descriptive study to look at what clinical and developmental characteristic are present amongst the sex offenders in Malaysia, which could be possible mitigating factors. Methods: Data was collected from offenders located in 3 prisons where the offenders are held. Results: a total of 147 prisoners participated in the study. Slightly more than half of the victims were below the age of 18, of which 10 were below the age of 12. Three quarters of offenders were thirty years and older, while 12 were below 18 years. However their problems begun much earlier in their life with 50 of the offenders reporting that they had difficulties in their primary support group, resulting in them feeling their families were less expressive, their parents were distant and unsupportive.29 of the offenders had not lived with their parents from the age of 16. More than half of the offenders reported academic, behavior and developmental difficulties; they reported losing interest in their studies and were struggling during their schooling days. 43 had history of aggressive behaviour during their adolescent years and 76 had peers who often indulged in risky behaviors. 85 of the offenders were Muslim. 40 made the criteria of Attention Deficit Hyperactive Disorder and conduct disorder while a quarter were diagnosed with having personality disorder. Slightly more than half of the offenders had alcohol and drug-related problems, 36 had history of previous crimes, mainly drug and theft offence. Conclusion: The findings show that the sex offenders are indeed a heterogeneous group with pervasive familial, behaviour, academic and social problems which are possible risk that can be identified early in the lives of offenders.